A laboratory study of individual recognition using Bewick’s Swan bill patterns - Brown, John; Lewis, Vivien (Wildfowl, 1977)
Observers were tested over five successive days for their ability to detect whether a pair of black and white slides were of the same or of a different Bewick’s Swan Cygnus columbianus bewickii. Matching of side views was more reliable than of front views. Although simultaneous matching was more reliable than successive, quite good matching was achieved under the latter condition. Matching was appreciably worse when the photograph of a matching pair were taken more than a year apart. Substantial variations were found between the observers in their willingness to assert a definite match. Training or calibration of observers in their use of judgment categories could prove beneficial.